2004
DOI: 10.1111/j.1601-5223.2004.01806.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climatic conditions on the mutations in pollen mother cells of Tradescantia clone 4430 and implications for the Trad-MCN bioassay protocol

Abstract: The present study was aimed at investigating the influence of relative humidity and temperature on spontaneous and pollution-induced mutation rates during exposure and recovery periods in the Trad-MCN test. Cuttings of Tradescantia clone 4430 were exposed to a negative control, to 4 mM maleic hydrazide (MH), and to a polluted water sample under varying conditions of air temperature and humidity in climatic chamber experiments. The relative humidity did not affect the spontaneous mutation rate in the clone inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 27 publications
(31 reference statements)
1
10
2
12
Order By: Relevance
“…The influence of weather conditions such as relative humidity, temperature and rainfall on the Trad-MCN assay as a result of exposure to genotoxic agents has been investigated by a number of studies (Klumpp et al, 2004;Savóia et al, 2009;Sisenando et al, 2011;Pereira et al, 2013). Corroborating Savóia et al (2009) and Sisenando et al (2011), we also observed an inverse relationship between the rate of MN and rainfall (Table 3).…”
Section: Discussionsupporting
confidence: 58%
“…The influence of weather conditions such as relative humidity, temperature and rainfall on the Trad-MCN assay as a result of exposure to genotoxic agents has been investigated by a number of studies (Klumpp et al, 2004;Savóia et al, 2009;Sisenando et al, 2011;Pereira et al, 2013). Corroborating Savóia et al (2009) and Sisenando et al (2011), we also observed an inverse relationship between the rate of MN and rainfall (Table 3).…”
Section: Discussionsupporting
confidence: 58%
“…However, in November 2012, the high temperature recorded in the urban environment of Taquara (mean of 34.3 °C) may have contributed to the increased MCN frequency. Temperature from 33 °C on under controlled conditions was reported as increasing spontaneous mutation rate of Tradescantia clone 4430 by Klumpp et al (2004). Air pollutants and stressful climatic conditions caused effects on the response of Tradescantia pallida var.…”
Section: Discussionmentioning
confidence: 99%
“…Frequencies obtained for negative controls remained below the background rate of up to 2.0 MCN/100 tetrads considered by Pereira et al (2013) as the result of spontaneous mutations that can occur naturally in the species, even when plants are grown in environments free from interference of any type of pollutant. In order to minimize any environmental interference before exposure, it is important that plants be allowed to adapt in controlled conditions (Ma et al, 1994;Klumpp et al, 2004). This procedure was employed in this study, following Cassanego et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…O teste de micronúcleo em Tradescantia pallida (Trad-MCN) é um dos bioensaios mais usados para o rastreamento de efeitos mutagênicos (Klumpp et al, 2004) e recentemente também vem sendo usado para detecção de efeitos antimutagênicos (Flores et al, 2003). Ele é baseado na formação de micronúcleos resultantes da quebra de cromossomos em células mãe de grão de pólen (Klumpp et al, 2004, Valadares et al, 2007.…”
Section: Introductionunclassified
“…Ele é baseado na formação de micronúcleos resultantes da quebra de cromossomos em células mãe de grão de pólen (Klumpp et al, 2004, Valadares et al, 2007.…”
Section: Introductionunclassified